Ownership versus Environment : Disentangling the Sources of Public Sector Inefficiency - Harrison, E. Ann (The World Bank, 2000)
January 2000 - Is public sector inefficiency due primarily to agency-type problems (ownership) or to the environment in which public enterprises operate (as measured by soft budget constraints or barriers to competition)? Both. Bartel and Harrison compare the performance of public and private sector manufacturing firms in Indonesia for 1981-95. They analyze whether public sector inefficiency is due primarily to agency-type problems (ownership) or to the business environment in which public enterprises operate, as measured by soft budget constraints or barriers to competition. They nest the two alternatives in a production function framework. The results, obtained from fixed-effects specifications, provide support for both models. The business environment matters. Only public enterprises that received loans from state banks or those shielded from import competition performed worse than private enterprises. Ownership matters. For a given level of import competition or soft loans, public enterprises perform worse than their counterparts in the private sector. Eliminating soft loans to Indonesia's public enterprises would raise total factor productivity by 6 percentage points; the same result could be achieved by increasing import penetration by 15 percentage points. Bartel and Harrison show that these findings are not due to selection effects for either privatization or the receipt of soft loans. This paper - a product of Poverty and Human Resources, Development Research Group - was part of a study funded by the Bank's Research Support Budget under the research project The Impact of Labor Market Policies and Institutions on Economic Performance (RPO 680-96). Ann Harrison may be contacted at aharriso@research.gsb.columbia.edu